Studi Tentang Pengaruh Shopee Paylater, Diskon Harga, Gratis Ongkos Kirim, Dan Online Customer Riview Terhadap Keputusan Pembelian Di E-Commerce Shopee (Studi Kasus Pada Konsumen Generasi Z Kec Lowokwaru Kota Malang) - Ilmi, Lilik Qaffidhotul; Arifin, Rois; Mahardani, Ahmad Subhan (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the influence of Shopee PayLater, price discounts, free shipping, and online customer reviews on purchase decisions on the Shopee e-commerce platform among Generation Z consumers in the Lowokwaru District, Malang City. This research is quantitative with an explanatory research approach. The sample used in this study consisted of 95 respondents, determined using the Maholtra formula based on the number of variable indicators. The results of the study indicate that simultaneously, Shopee PayLater, price discounts, free shipping, and online customer reviews significantly affect purchase decisions. Partially, Shopee PayLater, price discounts, and online customer reviews have a significant impact on purchase decisions, while free shipping does not have a significant influence. Keywords: Shopee PayLater, Price Discounts, Free Shipping, Online Customer Reviews, Purchase Decisions